KONSTRUKSI HUKUM PENATAUSAHAAN HASIL HUTAN DI KABUPATEN MAJALENGKA - Hidayat, Rahmat (HERMENEUTIKA : Jurnal Ilmu Hukum, 2015)
The Community forrest is a source of good supplier of the wood demand for the timber industry and the community. To ensure the right order of distribution of the forrest products, to protect private rights, and provide legal certainty to the community both producers and users of the forest products of the people, the Government has issued regulations regarding the administration of the forest products from the forrests rights. This study aims to determine whether the legal construction of the circulation of the forest products in the perspective of management of the forest products has known to the public and whether it has been providing solutions to the management of the forest products in the Regance of  Majalengka.The Construction law distribution of the forest products in the perspective of the management of the forest products largely unknown by the public in Majalengka. It is seen from the implementation of the distribution of the forest products in Majalengka that doesn?t use the document as a complete transport in the transport of the forest products, and as a proof of the validity of the forest products transported.The Construction law distribution of the forest products in the perspective of the management of the forest products hasn?t provided the solutions to the management of the forest products in the regance of Majalengka. This happens because of the regulations on the administration of the forest products originating from the private forest largely unknown by the public in Majalengka. otherwise it occurs due to less of a socialization, no incentive for publishers officials the Certificate of Origin, the less of enforcement by the authorities, the absence of the civil servants investigator and supervisor of the technical manpower for the sustainable forest management in the Forest Service Majalengka.Needs to be the disseminated of comprehensive and holistic by the relevant agencies of regarding the rules and the regulations of the forest product administration, namely West Java of the Provincial Forrest Service, the Forrest Products of the Monitoring distribution center of Jakarta Region VII Production and the Forestry Office Majalengka. Additionally need the involvement of all components outside the government that the people (owners of folk wood) and the businesses wood of the forest products.